Estado del arte de los estudios sobre conducta suicida en población privada de la libertad (2021)
The suicide in a population deprived of freedom (PPL) in detention centers in the city of Bogotá, for the commission of different crimes, brings with it a series of questions and questions that generate concern, doubt and sometimes fear; In this document you will find the main studies, research and technical documents made by officials and academics, among others. The objective was to establish the state of the  art of the studies carried out and the trends found regarding suicidal behavior in this population. Suggestions and recommendations for its approach and prevention are given around the problem studied.